(untitled) (Darya Ganj, New Delhi, 2005)
Contents of material: 1/ Economics of information and knowlege. 2/ Continuing professional development of LIS teachers: A strategy. 3/ Role of harijan welfare libraries among rural women. 4/ Academic status of librarians in the universities in kerala: An analytical study. 5/ Bibliometric analysis of the jounal "AMBIO". 6/ Emerging technologies for Hi-Tech libraries. 7/ User education in collecge libraries of kerala in the IT era: An analytical study. 8/ Library and information science literature in Malayalam. 9/ Library management software in India: A comparative assessment of leading packages. 10/ Niya archives: digital library software using CDS/ISIS. 11/ Digitization of indigenous materials: problems and solutions in the context of Kerala university. 12/ Sociology of information and rural information service. 13/ Bridging the digital divide. 14/ Scientific productivity of agricultural scientists: A scientometric study. 15/ Organisation and utilisation of media libraries
Keywords: Libraries,Digital library,Libraries and electronic publishing; Electronic information resources